COVID-19 clinical presentation, management, and epidemiology: a concise compendium - Maison, David P.; Tasissa, Hawi; Deitchman, Amelia; Peluso, Michael J.; Deng, Youping; Miller, F. DeWolfe; Henrich, Timothy J.; Gerschenson, Mariana (Frontiers in Public Health, 2025)
Coronavirus Disease 2019, caused by severe acute respiratory coronavirus 2, has been an ever-evolving disease and pandemic, profoundly impacting clinical care, drug treatments, and understanding. In response to this global health crisis, there has been an unprecedented increase in research exploring new and repurposed drugs and advancing available clinical interventions and treatments. Given the widespread interest in this topic, this review aims to provide a current summary—for interested professionals not specializing in COVID-19—of the clinical characteristics, recommended treatments, vaccines, prevention strategies, and epidemiology of COVID-19. The review also offers a historical perspective on the pandemic to enhance understanding.